LITERATURE REVIEW EFEKTIVITAS AROMATERAPI LAVENDER DALAM MENURUNKAN NYERI PADA PASIEN OPERASI SECTIO CAESAREA - Raisa Rosselini (LPPM STIKes Mitra Adiguna, 2022)
The amount of sectio caesarea surgery in Indonesia according to National Survey data in 2013 are approximately ± 1.200.000 from ± 5.690.000 labor or around 24,8% from every labor. One of the uncomfortable moment for the post sectio casearea surgery patient is pain around their surgery wound. To reduce the pain, we can use the pharmacology teraphy or non pharmacology teraphy. The lavender aromateraphy is one of the example of non pharmacology teraphy. This research are using literature review techniques. From 15 journal that has been reviewed, the efectiveness of lavender aromateraphy can reduce pain in post sectio caesaria surgery patient. Based on the result, we can conclued that lavender aromateraphy can be efective to reduce pain in post sectio caesarea surgery patient. According to the researcher, lavender can be usefull to reduce pain in post sectio caesarea surgery patient and turn the patient’s physical to a better condition after smelling the lavender aromateraphy.